Analisis Kelayakan Dan Strategi Pengembangan Wilayah Dalam Wacana Pembentukan Daerah Otonom Baru Provinsi Sumatera Tengah - Akbar Yudha Baskara; Alpon Satrianto (Media Riset Ekonomi Pembangunan (MedREP), 2026)
The discourse on the establishment of Central Sumatra Province aims to assess regional feasibility and formulate development strategies for a prospective autonomous region (DOB). This study applies a descriptive quantitative approach using a scoring method based on Government Regulation Number 78 of 2007. Supporting analyses include fiscal autonomy degree, Location Quotient (LQ), Klassen Typology, and SWOT analysis. The findings show that the proposal has been submitted by community leaders, but no official approval has been issued by the central government. Technically, all proposed regions, namely Sijunjung, Dharmasraya, South Solok, Kuantan Singingi, Kerinci, Bungo, and Sungai Penuh City, have not met the feasibility threshold during 2020-2024, particularly in regional potential and financial capacity indicators. Fiscal independence remains low, averaging only 9.01%, indicating strong dependence on central government transfers. The regional economy is still dominated by the primary sector, except in Sungai Penuh City and Bungo Regency, where the service sector is more developed. Therefore, strengthening fiscal capacity, optimizing local revenue, downstreaming leading commodities, and improving human resources and infrastructure should become priorities before regional expansion is implemented.